Long sequence of relativistic electron bunches as a driver in wakefield method of charged particles acceleration in plasma - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Using LCODE 2.5D-simulation of wakefield excitation in plasma by a long sequence of relativistic electron bunches was performed. For the resonant sequence wakefields add coherently until the wave nonlinearity comes into play. The mechanism is found out which enables resonant excitation of the wakefield even if the bunch repetition frequency appreciably differs from the plasma frequency. Conditions for enhancement of excitation efficiency, acceleration gradient, and transformation ratio were investigated. С использованием LCODE проведено 2.5-мерное численное моделирование возбуждения кильватерных полей в плазме длинной последовательностью релятивистских электронных сгустков. Для резонансной цепочки кильватерные поля складываются когерентно, пока существенной не становится нелинейность волны. Обнаружен механизм, который делает возможным резонансное возбуждение кильватерного поля, даже если частота следования сгустков отличается от плазменной частоты. Исследованы условия повышения эффективности возбуждения, темпа ускорения и коэффициента трансформации. З використанням LCODE проведено 2.5-вимірне чисельне моделювання збудження кільватерних полів у плазмі довгою послідовністю релятивістських електронних згустків. Для резонансної послідовності кільватерні поля додаються когерентно, поки не стає суттєвою нелінійність хвилі. Виявлено механізм, який забезпечує резонансне збудження кільватерного поля, навіть якщо частота слідування згустків суттєво відрізняється від плазмової частоти. Досліджено умови збільшення ефективності збудження, темпу прискорення та коефіцієнта трансформації енергії.